2005
DOI: 10.1080/09298210500236325
|View full text |Cite
|
Sign up to set email alerts
|

Chord span and other chordal characteristics affecting connections between perceived closeness and set-class similarity

Abstract: The importance of chord span for estimations of closeness (similarity or resemblance) was examined. The subjects (musically trained and less-trained) were asked to rate closeness between pentachords with spans varying from 6 to 22 semitones. Closeness estimations were found to be only weakly correlated with theoretical similarities calculated by eleven similarity measures. The factors that did guide closeness estimations were analysed using regression analysis and multidimensional scaling. Chord span, common p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
2
9
0
1
Order By: Relevance
“…Subset-class relation seemed to be important only if the relation was represented by common pitches, in other words literally as a chord and a subchord, or by similar intervals. Thus the present study confirmed the importance of the number of common pitches for closeness estimations (reported earlier by Bruner, 1984;Gibson, 1993;Kuusi, 2001Kuusi, , 2005bLane, 1997;Williamson & Mavromatis, 1999). Previous studies have also shown that chordal characteristics are more important than abstract properties for estimations (Bruner 1984;Gibson, 1988Gibson, , 1993Samplaski, 2000).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Subset-class relation seemed to be important only if the relation was represented by common pitches, in other words literally as a chord and a subchord, or by similar intervals. Thus the present study confirmed the importance of the number of common pitches for closeness estimations (reported earlier by Bruner, 1984;Gibson, 1993;Kuusi, 2001Kuusi, , 2005bLane, 1997;Williamson & Mavromatis, 1999). Previous studies have also shown that chordal characteristics are more important than abstract properties for estimations (Bruner 1984;Gibson, 1988Gibson, , 1993Samplaski, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have also shown that chordal characteristics are more important than abstract properties for estimations (Bruner 1984;Gibson, 1988Gibson, , 1993Samplaski, 2000). In certain studies however, abstract concepts were found to play a key role in estimations (Kuusi, 2001(Kuusi, , 2005a(Kuusi, , 2005bSamplaski, 2004;Williamson & Mavromatis, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The idea has strong relations with the continuum between conceptually-based and perceptually-driven similarity (Goldstone, 1994). Many experiments have studied perception of post-tonal chords in ways that enhance surface-level characteristics and enable perceptually-driven estimations (Bruner, 1984;Gibson, 1993;Kuusi, 2001Kuusi, , 2005aSamplaski, 2000). The abstract-level similarity of post-tonal chords has thus far been studied only in a few experiments (Kuusi, 2005b(Kuusi, , 2007(Kuusi, , 2010, and all of them have compared chords representing different set-classes.…”
Section: Tonal and Post-tonal Chordsmentioning
confidence: 99%